Stability parameters in upland cotton cultivars - Santana, João Cecílio Farias de; Cavalcanti, Fernando Bezerra; Santos, Elton Oliveira dos (Pesquisa Agropecuaria Brasileira, 2014)
Stability parameters for yield from nine cultivars of upland cotton were studied in a 7 x 7 latin square arrangement, in a two-year period, 1977/78 to 1978/79. Five of these cultivars were common for the two years while the others varied with the year. The data for the analysis were obtained from the seed-cotton yield in kg/ha, of the "Ensaio Nacional de Cultivares de Algodão" (National Canon Variety Test) planted in the States of Pará, Maranhão, Ceará, Rio Grande do Norte, Paraíba, Pernambuco, Alagoas, Bahia and Minas Gerais, in a total of 26 tests at 20 different environments of the North and Northeast of Brazil. The combined analysis of variance through the F test showed significant effects for cultivars, environments, the interactions cultivars x environments, environment linear, cultivars x environments (linear) and deviation from regression. In 1977/78, the most stable cultivars were BR 1, IAC 18 and SL 7-1 with the cultivar Allen 333-57 being the least stable, although it had the highest yield (1,918 kg/ha). In 1978/79, IAC 12-2RB, IAC 18 and BR 1 were the most stable cultivars while Allen 333-57, IAC 13-1, BR-1 and SL 7-1 were the least stable ones.